Trade-based manipulation: Beyond the prosecuted cases - Neupane, Suman; Rhee, S. Ghon; Vithanage, Kulunu; Veeraraghavan, Madhu (Journal of Corporate Finance, 2017)
Using insights from prosecuted cases, we present compelling evidence of large-trade based manipulation in a sizeable number of Indian IPOs that, in all likelihood escaped enforcement actions. Consistent with the pump-and-dump scheme these IPOs exhibit abnormally high volume of large trades, a significant fraction of which originates from a syndicate of traders present in the prosecuted IPOs. More importantly, stock price in the manipulated IPOs rises initially on account of artificial trades, but then declines significantly as the manipulators exit the market. Interestingly, not all attempts at manipulation are entirely successful as stock price in some of the manipulated IPOs crash on the first day of listing.